(untitled) (UNED Research Journal, 2018)
Onychophoran worms seldom attack spiders because spiders are agile and dangerous prey. Here we report an onychophoran feeding on a spider (possibly a Ctenidae) in Sierra Llorona, Colón, Panamá (9,35863°-79,70287°; altitude 491 m).